Oral health-related quality of life among 11-12year old indigenous children in Malaysia - Nordin, Eizatul Aishah Berhan; Shoaib, Lily Azura; Mohd Yusof, Zamros Yuzadi; Manan, Nor Malina; Othman, Siti Adibah (BioMed Central, 2019)
BackgroundPoor oral health among Malaysian indigenous Orang Asli (OA) children may impact on their daily performances.AimTo assess the oral health status, related behaviours, and oral health-related quality of life (OHRQoL) among OA children in Cameron Highlands (CH), Malaysia, and to identify the predictor(s) for poor OHRQoL.DesignThis was a cross-sectional study involving 249, 11-12year old OA children from 4 OA primary schools in CH. The children completed a self-administered questionnaire comprising information on socio-demographics, oral health-related behaviours, and the Malay Child Oral Impacts on Daily Performances (Malay Child-OIDP) index followed by an oral examination. Data were entered into the SPSS version 23.0 software. Non-parametric tests and multiple logistic regression were used for data analysis.ResultsThe response rate was 91.2% (n=227/249). The prevalence of caries was 61.6% (mean DMFT=1.36, mean dft=1.01) and for gingivitis was 96.0%. Despite the majority reported brushing their teeth >= 2x/day (83.7%) with fluoride toothpaste (80.2%), more than two-thirds chewed betel nut >= 1/day (67.4%). Majority of the children (97.8%) had a dental check-up once a year. Nearly three-fifths (58.6%) reported experiencing oral impacts on their daily performances in the past 3months (mean score=5.45, SD=8.5). Most of the impacts were of very little to moderate levels of impact intensity with 90.2% had up to 4 daily performances affected. Most of the impacts were on eating (35.2%), cleaning teeth (22.0%) and relaxing activities (15.9%). Caries in primary teeth is associated with oral impacts among the OA children.ConclusionsThe 11-12year old OA children in Cameron Highland had high prevalence of caries and gingivitis with the majority chewed betel nut regularly. Caries in primary teeth is associated with poor OHRQoL. Future programmes should target younger age group children to promote positive oral hygiene practices, reduce caries, and improve quality of life.